Studi Netnografi Akun Instagram @Quranreview dalam Menyampaikan Dakwah Kepada Gen Z - Ulfa Azkia; Hasan Basri M. Nur; Zainuddin T (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the forms of da'wah message delivery and the patterns of digital social interaction found on the Instagram account @quranreview targeting Generation Z. The research employs a qualitative descriptive approach using netnography as the main method, and the AIDA model (Attention, Interest, Desire, Action) as the analytical framework to assess the effectiveness of digital da'wah communication. Data were collected through observations of content and comment interactions published between January and April 2025. The findings reveal that @quranreview successfully applies the full AIDA model in its content, starting with distinctive visuals and relevant topics to attract attention, reflective narratives that sustain interest, empathetic language that evokes spiritual desire, and finally encouraging real actions such as sharing content, engaging in discussions, and joining online da'wah activities. The digital social interactions show active, empathetic, and reflective two-way communication. Audiences are not merely passive recipients of messages but actively construct meaning through comments, personal stories, and spiritual discourse. This study concludes that @quranreview delivers relevant, engaging, and participatory digital da'wah and successfully creates a dialogical space that aligns with the communication characteristics of Generation Z on social media.